Prevalence of melanoma and nonmelanoma malignancies in patients visiting dermatology clinics in Ardabil City, 2002-2013 - Mohebbipour, Alireza; Amani, Firouz (International Journal of Advances in Medicine, 2017)
Background: BCC and SCC are the most prevalent malignant non-melanoma skin tumors. BCC is the most common skin tumor in white-skinned people, and as one ages, after being 40 year-old, incidence rate of BCC increases. SCC has the next rank and is more common in middle-aged and old persons. The present study addresses the prevalence of melanoma and non-melanoma malignancies in patients visiting dermatology clinics in Ardabil during 2002-2013. Methods: This study was of retrospective descriptive type. Approximately out of 100000 medical records of patients visiting dermatology clinics, 371 cases were chosen. The selected cases had undergone biopsy on suspicion of malignancy and their pathological response was attached to the record. Data were analyzed through SPSS, version 19, and descriptive as well as inferential statistical tests were used. Results: The prevalence of malignant skin tumors was 0.37%. 48% of cases were male, and 52% were females. The mean age of patients was 62.4 with a standard deviation of 15, and individuals of 50-70 age range had the peak incidence (46.1%). BCC was the most prevalent lesion (72%). Nose was the most common area for skin tumors (35.6%). For BCC the mean age was 62 ± 14, and for SCC it was 64.6 ± 17. Conclusions: According to the results, BCC was the most prevalent tumor. Skin tumors were mostly observed among females, and the most common locus was nose.